Modern slavery in the UK: how should the health sector be responding?. (20th December 2018) - Such, Elizabeth; Jaipaul, Ravi; Salway, Sarah
ABSTRACT: Modern slavery is crime of extreme exploitation. It includes the use of coercion, force, deception and abuse of vulnerability for such purposes as trafficking, labour, sexual exploitation, forced criminal activity and domestic servitude. It is a topic of growing interest in the UK and beyond as it has emerged as an issue of considerable scale and consequence. To date, debates have been dominated by a law enforcement perspective. Less apparent has been an articulation of the implications of modern slavery for the health sector. This is despite growing evidence of the dire physical and mental health consequences for survivors. This paper addresses this gap by examining a series of issues relevant to UK health systems. After describing what is modern slavery and the nature of the problem, we identify how the health sector has responded to date. We then articulate how health services and public health can more coherently and systematically meet the challenges of modern slavery through policy and practice. Finally, we present a call for the health sector to position itself as a central to the wellbeing of survivors and as a fundamental ally in modern slavery prevention.